Zinc Vacancy-Induced Room-Temperature Ferromagnetism in Undoped ZnO Thin Films. (16th August 2012) - Ren, Hongtao; Xiang, Gang; Gu, Gangxu; Zhang, Xi; Wang, Wenjun; Zhang, Peng; Wang, Baoyi; Cao, Xingzhong
Abstract : Undoped ZnO thin films are prepared by polymer-assisted deposition (PAD) and treated by postannealing at different temperatures in oxygen or forming gases (95% Ar + 5 % H2 ). All the samples exhibit ferromagnetism at room temperature (RT). SQUID and positron annihilation measurements show that post-annealing treatments greatly enhance the magnetizations in undoped ZnO samples, and there is a positive correlation between the magnetization and zinc vacancies in the ZnO thin films. XPS measurements indicate that annealing also induces oxygen vacancies that have no direct relationship with ferromagnetism. Further analysis of the results suggests that the ferromagnetism in undoped ZnO is induced by Zn vacancies.